2006
DOI: 10.1002/ana.20938
|View full text |Cite
|
Sign up to set email alerts
|

Lack of nigrostriatal pathology in a rat model of proteasome inhibition

Abstract: Systemic administration of ubiquitin-proteasome system inhibitors to rodents has been reported to induce certain behavioral and neuropathological features of Parkinson's disease. The goal of this study was to replicate these observations by administering a proteasome inhibitor (PSI) to rats using McNaught and colleagues' protocol. No alterations in locomotor activity or striatal dopamine and its metabolites were observed. Differences in nigral dopaminergic cell number between proteasome inhibitor- and vehicle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…In some experimental conditions, mainly after subcutaneous administration of PSI, a loss of SN dopaminergic neurons was observed and varied between 40% [38] and 50% [51], and even exceeded 50% [33]. Four other groups of researchers, despite the fact that they tried faithfully to follow the experimental protocol proposed by McNaught et al, failed to replicate the results described earlier [6,22,23,30]. Our results support the theory of McNaught et al…”
Section: Discussionsupporting
confidence: 78%
“…In some experimental conditions, mainly after subcutaneous administration of PSI, a loss of SN dopaminergic neurons was observed and varied between 40% [38] and 50% [51], and even exceeded 50% [33]. Four other groups of researchers, despite the fact that they tried faithfully to follow the experimental protocol proposed by McNaught et al, failed to replicate the results described earlier [6,22,23,30]. Our results support the theory of McNaught et al…”
Section: Discussionsupporting
confidence: 78%
“…Two known genetic causes of PD involve aspects of UPS function (Parkin and UCH-L1), and α-syn is a substrate for the UPS. Reduced UPS activity has been found in brains of sporadic PD patients [48,49] and some investigators have found that administration of UPS inhibitors to rodents can recreate some of the features of PD, although these models remain controversial [50][51][52][53][54][55]. Finally, we have found that several commonly used pesticides inhibit the UPS and are associated with an increased risk of developing PD [7,13].…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, decreased locomotor activity was reported to occur in response to PSI treatment. However, since this report three other papers have failed to replicate various aspects of the original findings (Bove et al, 2006;Kordower et al, 2006;Manning-Bog et al, 2006), while two other papers have replicated aspects of the orginal report (Schapira et al, 2006;Zeng et al, 2006).…”
Section: Introductionmentioning
confidence: 85%